In Silico modeling of immune-cardiovascular-endocrine interactions - Windoloski, Kristen A; T Ottesen, Johnny; Olufsen, Mette S (Journal of Cardiovascular Medicine and Cardiology, 2022)
The immune system provides an intricate, balanced response to combat the effects of inflammatory stimuli. It incorporates both positive and negative feedback from multiple physiological systems such as the cardiovascular and endocrine systems including mechanisms functioning on a variety of time scales. They have been studied individually via scientific experiments and using mathematical modeling. However, more analysis is needed to study the interactions between these three systems during an inflammatory event. We present the first dynamical systems model studying immune, cardiovascular and endocrine responses to a 2 ng/kg bolus dose of endotoxin. The model is calibrated to experimental data from two endotoxin challenge studies and we use this model to investigate the effects of endotoxin dosage, administration timing and administration method. Our model shows that most repercussions of endotoxin administration clear the system within 24 hours, but effects can linger for up to 72 hours.